1997
DOI: 10.1007/bf02594581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of riluzole on the evolution of focal cerebral ischemia: a magnetic resonance imaging study

Abstract: The aim of this study was to investigate the effects of riluzole on the lesion induced by a permanent middle cerebral artery occlusion (MCAO) in rats. Riluzole at 4 or 8 mg/kg i.v. significantly reduced the cortical ischemic brain damage. With the most effective dose of 8 mg/kg, the time evolution of the lesion was assessed by T2-weighted magnetic resonance imaging (MRI) repeated on the same animals after MCAO. MRI obtained at 24, 48, and 72 hours after MCAO showed a progressive increase of the ischemic lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Takagaki et al (18) showed that infarction in the striatum developed during the early stage (within 6 h) after MCA occlusion and that development of cortical infarction was slower than that seen in the striatum after permanent occlusion of MCA according to the method of Tamura et al (3). On the other hand, it was reported that the ischemic region in the MRI analysis increased progressively over a few days after the occlusion of MCA in rats (19,20). Furthermore, neuroprotective effects have been noted with the delayed treatment of some drugs, such as the Na + / Ca 2+ channel blocker NS-7 (21) and the low molecular weight heparin enoxaparin (22), in rats subjected to MCA occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Takagaki et al (18) showed that infarction in the striatum developed during the early stage (within 6 h) after MCA occlusion and that development of cortical infarction was slower than that seen in the striatum after permanent occlusion of MCA according to the method of Tamura et al (3). On the other hand, it was reported that the ischemic region in the MRI analysis increased progressively over a few days after the occlusion of MCA in rats (19,20). Furthermore, neuroprotective effects have been noted with the delayed treatment of some drugs, such as the Na + / Ca 2+ channel blocker NS-7 (21) and the low molecular weight heparin enoxaparin (22), in rats subjected to MCA occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrospinal fluid, specified as voxels with T 2 values at least 4.5 standard deviations higher than mean normal contralateral values (from 65 control rats), was excluded in further analysis. Infarcted tissue was automatically identified as voxels with T 2 values at least 2 standard deviations higher than mean contralateral graymatter values on poststroke day 3 (Group I) or 7 (Groups II and III) (T 2 -based lesion sizes at day 3 after permanent MCAo or at day 7 after embolic stroke have been shown to correspond with infarction size on postmortem histologic sections 23,24 ). Acute perfusion abnormality was similarly identified on acute MTT values.…”
Section: Image Processingmentioning
confidence: 99%
“…One of the two neuroprotective agents is riluzole, used for treatment of amyotrophic lateral sclerosis. The neuroprotective effect of riluzole has been well established through focal cerebral ischaemia, spinal cord injury and retinal ischaemia cases (Mottet et al. 1997, Ettaiche et al.…”
Section: Discussionmentioning
confidence: 99%
“…One of the two neuroprotective agents is riluzole, used for treatment of amyotrophic lateral sclerosis. The neuroprotective effect of riluzole has been well established through focal cerebral ischaemia, spinal cord injury and retinal ischaemia cases (Mottet et al 1997, Ettaiche et al 1999, Lang-Lazdunski et al 1999. A possible protection mechanism of riluzole is related to the fact that it inhibits synaptic glutamate release by the reduction of voltage-gated Na + channels and it therefore attenuates excitotoxic neuronal death (Doble 1996).…”
Section: Discussionmentioning
confidence: 99%